Looking at “Us”, Attending to “Them”, Seeking the Divine: Revisiting Disability in the Christian Tradition - Brock, Brian (Journal of religion, disability & health, 2013)
This article responds to the reflections on Disability in the Christian Tradition that are collected in this journal issue, especially those of Amos Yong, Deborah Beth Creamer, Elizabeth Antus, Willie James Jennings, and John Goldingay. It discusses some of the metatheoretical issues at stake as these scholars attempt to allow thinkers from the past shape their own contemporary thinking, and it indicates some of the reasons why this type of engagement might be understood to play an important role in attempts to renew contemporary practice.